Ocular adnexal lymphoma – A single-center observational study of survival outcomes - Karuvel Kannan Saraswathi; Pragya Saini; Radhakrishnan Santhi; Veerappan Muthukkaruppan; Ayyasamy Vanniarajan; Usha Kim (Indian Journal of Ophthalmology)
Purpose: This study aims to comprehensively characterize the clinical, demographic, and histopathological features of ocular adnexal lymphoma (OAL) and assess their impact on patients’ survival outcomes. Methods: A total of 123 patients were included in the study; of these, 93 patients were selected for survival analysis. Survival data were analyzed using the Kaplan-Meier test, and correlation was assessed through the log-rank test and Cox regression analysis. Results: The median age at presentation was 56 years. Furthermore, 98% of patients had primary OAL. The orbit was the most common site of involvement. The majority of patients were of B-cell origin (98%), and only 2% of patients had T-cell lymphoma. In addition, 83% of patients were treated with chemotherapy, and with a median follow-up of 38 months, complete remission was achieved in 48% of patients. The median progression-free survival was 26.4 months. The presence of disseminated disease was strongly linked to an unfavorable prognosis (P < 0.001) and reduced survival (P = 0.037). Conclusion: The 5-year overall survival of the entire study cohort was 81%. The prognosis for OAL is found to be favorable, but the presence of dissemination serves as a notable predictor for poor prognosis.